Choosing Cell Fate Through a Dynamic Cell Cycle - Chen, Xinyue (Curr Stem Cell Rep, 2015)
A close relationship between proliferation and cell fate specification has been well documented in many developmental systems. In addition to the gradual cell fate changes accompanying normal development and tissue homeostasis, it is now commonly appreciated that cell fate could also undergo drastic changes, as illustrated by the induction of pluripotency from many differentiated somatic cell types during the process of Yamanaka reprogramming. Strikingly, the drastic cell fate change induced by Yamanaka factors (Oct4, Sox2, Klf4, and c-Myc) is preceded by extensive cell cycle acceleration. Prompted by our recent discovery that progression toward pluripotency from rare somatic cells could bypass the stochastic phase of reprogramming and that a key feature of these somatic cells is an ultrafast cell cycle (~8 h/cycle), we assess whether cell cycle dynamics could provide a general framework for controlling cell fate. Several potential mechanisms on how cell cycle dynamics may impact cell fate determination by regulating chromatin, key transcription factor concentration, or their interactions are discussed. Specific challenges and implications for studying and manipulating cell fate are considered.